Transport and Means of Communication in Language Worldview of Vologda Peasant: Traditions and Innovations - E. N. Ilyina (Научный диалог)
The article is devoted to the study of records of dialect speech, verbalizing the ideas of rural residents of the Vologda region about the system of transport and means of communication. The object of analysis is the lexical set of names of vehicles and means of communication, as well as the corpus of texts. Informants differentiate roads in detail from the point of view of the possibilities of their use in summer or winter, for walking, skiing, wheeled, sledge, caterpillar, sled, etc. transportation. Many traditional beliefs and customs of dialect speakers are associated with the road. Informants living near navigable rivers and large lakes perceive movement by water as one of the ordinary components of the transport system, while those living far from water bodies treat water transport with caution and prejudice, emphasizing the danger of the water element. The most vivid impressions of dialect speakers about movement in space are associated with air transport. The narrative of this event is clothed in the genre form of a “story-plate”, which occupies an intermediate position between everyday and folklore non-fairy-tale prose. However, such stories, as a rule, tell about the first or only air flight in the life of the informant.